2004
DOI: 10.1074/jbc.m307341200
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Targeting of Conserved Cryptic Epitopes of Infectious Agents by Single Domain Antibodies

Abstract: Antigen variation is a successful defense system adopted by several infectious agents to evade the host immune response. The principle of this defense strategy in the African trypanosome paradigm involves a dense packing of variant surface glycoproteins (VSG) exposing only highly variable and immuno-dominant epitopes to the immune system, whereas conserved epitopes become inaccessible for large molecules. Reducing the size of binders that target the conserved, less-immunogenic, cryptic VSG epitopes forms an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
188
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(196 citation statements)
references
References 44 publications
2
188
1
5
Order By: Relevance
“…Stijlemans et al . 68 hypothesized that the ability of a dromedary V H H, cAb-An33, to target a cryptic glycopeptide epitope conserved across all variant surface glycoprotein classes of Trypanosoma brucei was due to the V H H’s small size as well as, potentially, the nature of this epitope. This hypothesis was supported by the inability of rabbit and dromedary polyclonal conventional antibodies as well as a ~90-kDa lectin to access this site.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stijlemans et al . 68 hypothesized that the ability of a dromedary V H H, cAb-An33, to target a cryptic glycopeptide epitope conserved across all variant surface glycoprotein classes of Trypanosoma brucei was due to the V H H’s small size as well as, potentially, the nature of this epitope. This hypothesis was supported by the inability of rabbit and dromedary polyclonal conventional antibodies as well as a ~90-kDa lectin to access this site.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…No studies have reported hapten-specific V NAR s, and only one study has described a carbohydrate-specific V H H directed against Neisseira meningitidis lipopolysaccharide; 120 at least two camelid V H Hs have been described that bind to glycopeptide epitopes. 68,76 No sdAbs of any type have been described that convincingly bind lipids or nucleic acids. Together, the consensus of the data is that it is probably difficult, but not impossible, for sdAb paratopes to accommodate haptens and that three CDRs are sufficient to form the binding pockets and grooves required for such interactions, although potential involvement of solubility-enhancing FR2 residues at the former V L interface in pocket formation may impose restrictions on hapten-binding specificities.…”
Section: Single-domain Antibodies Directed Against Small Moleculesmentioning
confidence: 99%
“…sVSG was prepared by osmotic shock as described previously [78]. Briefly, the DE52-purified parasites were resuspended in Balts-buffer (50 mM sodium phosphate buffer, pH 5.5) and incubation on ice for 30 min followed by a 5-min incubation at 371C.…”
Section: Vsg Preparations and Lps Quantificationmentioning
confidence: 99%
“…Ces anticorps dénommés HcAb pour heavy chain only antibodies lient leurs cibles par un seul domaine variable nommé VHH pour le différencier des VH conventionnels (Figure 1 [12] (➜). Les dAb peuvent aussi cibler des épitopes conservés et peu accessibles sur certaines protéines d'agents infectieux qui ont évolué pour présenter aux anticorps conventionnels des épitopes dominants hypervariables [13]. Par leur taille et leur structure, les dAb sont donc une source potentielle d'anticorps antiviraux neutralisants à spectre large [14].…”
Section: L'origine Des Single Domain Antibodies (Dab)unclassified